Matsuda Denjūrō’s Service in Hakodate and the Surrounding Area From October 31, 1799, to January 1, 1801 (Based on the Tales of the Northern Barbarians) - A. V. Klimov (Russian Japanology Review)
The manuscript Tales of the Northern Barbarians (Hokuidan, 「北夷談」) by Matsuda Denjūrō (松田伝十郎, 1769–1843) is a valuable source on the history of Russian-Japanese relations, the development of the northern territories inhabited by the Ainu conducted by the Japanese, relations between the Ainu and the Japanese, their barter trade. The written source consists of seven notebooks. The manuscript was created in the first years of the Bunsei era (文政, 1818–1831). It describes the events from 1799 to 1822 in chronological order, i.e., events that occurred during the 24 years of Matsuda’s service in the lands of the Ainu. The manuscript is written in cursive (Japanese: “grass writing”, sōsho 草書). The second half of the first book examines the bear festival and the inau, cult objects of the Ainu, which were described in detail by the author in [Klimov A.V. 2024]. This article is the continuation of the description of the events of the first notebook, in which Matsuda describes: wintering in Akkeshi, the life and clothing of the Ainu, the peculiarities of hunting sea lions, the attitude towards the moon fish, wintering in Aputa, the fight against the smallpox epidemic that arose, and his return to Edo. The text is accompanied by numerous sketches. The illustrations in the manuscript are of great value, providing additional information that is missing from the text itself. Matsuda’s descriptions refer to November 1799 – January 1801. The Hokuidan manuscript has not yet been translated into any of the European languages other than Russian. The author of this article provides translations of fragments of the written source in the chapters of published collective monographs [Klimov A.V. 2020; Klimov A.V. 2021; Klimov A.V. 2022]. The translation was carried out from the published text of the Japanese manuscript in the ten-volume series of written monuments entitled Collection of Historical Materials About the Life of the Common People of Japan (Nihon shomin seikatsu shiryō shū sei 日本庶民生活史料集成), in the fourth volume [Matsuda 1969]. In addition to this series, the Tales were published in Old Japanese in the fifth volume of a six-volume series of written monuments called Library: Northern Gate (Hokumon sō sho 北門叢書), published in 1972.